Firm and product survival analysis: Evidence from South African tax administrative and product data - Syden Mishi; Weliswa Matekenya; Leward Jeke; Ronney M. Ncwadi; Roseline T. Karambakuwa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Enterprise development, especially expansion into export markets, is essential to create employment and unlock growth potential in many economies, including in sub-Saharan Africa. However, both firm and product survival (mainly in the export market) is not sufficiently documented to inform business development and export growth strategies. Using the South African National Treasury and UNU-WIDER CIT-IRP5 firm panel 2008-17 data set (version 3.4), we employ parametric and non-parametric methods to analyse the survivor function and hazard (exit) rate of firms and exported products, across the whole sample and by groups (such as sector, firm size, location (province), and membership of a special economic zone, among other categorizations). Our study enables an understanding of the survival rate of South African firms across different sectors, estimated with robust techniques (compared with the descriptive statistics that are usually relied on). The key issues investigated are South African products' survival in the export market and the overall determinants of survival, to inform support for firms and export promotion strategies. The results show that firm survival depends on the nature of the market, that is, the firm type and product characteristics. Similarly, products' survival is dependent mostly on the nature of the market.
Keywords: C14; D22; L25; L52; 330; enterprise development; firm survival; product survival; export market; employment; special economic zone